Representasi perempuan dalam film Like & Share: Analisis wacana kritis Sara Mills - Rosita, Farida Yufarlina; Hastuti, Dwi Puji (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study aimed to describe how women are portrayed in the Like & Share film by Gina S. Noer. This study uses a descriptive qualitative methodology and examines Sara Mills' Critical Discourse Analysis. The role of women in movies is discussed in this study, focusing on how they are portrayed in stories, characters, and visuals. The information used in this study was gathered through observation and documentation methods and takes the shape of conversation, narration, characterization, and visual representations of female characters in movies. Researchers frequently and thoroughly viewed the film, noting significant details about the study's goals. The findings demonstrated that as the story progressed in the movie, women's status changed from object to subject. Like & Share also succeeded in dismantling patriarchal power relations in the representation of women and providing space for female characters to have agency over their traumatic experiences. The audience is not only positioned as passive observers but is also presented in an empathic position to be able to assess and understand the reality of women victims of digital-based sexual violence.